2022
DOI: 10.3389/fcvm.2022.892025
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Cement entrapped in the inferior vena cava filter after pedicle screw augmentation

Abstract: BackgroundCement leakage into the inferior vena cava (IVC) is one of the most common complications associated with cement vertebroplasty, and can lead to potentially life-threatening complications such as pulmonary cement embolism (PCE). Implantation of an IVC filter is effective in the prevention of fatal pulmonary embolism. Here, we present an extremely rarely case of cement entrapped in an IVC filter after pedicle screw augmentation, and discuss all similar cases reported in the literature.Case presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Although the number of studies (number of cases) reporting this issue are limited, this may be an anatomical note to keep in mind when performing CAPS. The relationship between the IVC and lumbar vein and characteristics of the lumbar vein need to be discerned, because intraoperative cement leakage into the IVC significantly contributes to PCE [ 68 ]. The lumbar veins enter the IVC at the L1-L5 vertebral positions, and cement flow into the IVC may result from the numerous connections to the vertebral and branch veins, lack of valves in the internal and external venous plexus, marked venous enlargement in older individuals, and lower pressure in the vertebral venous system than in the pelvic veins [ 34 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of studies (number of cases) reporting this issue are limited, this may be an anatomical note to keep in mind when performing CAPS. The relationship between the IVC and lumbar vein and characteristics of the lumbar vein need to be discerned, because intraoperative cement leakage into the IVC significantly contributes to PCE [ 68 ]. The lumbar veins enter the IVC at the L1-L5 vertebral positions, and cement flow into the IVC may result from the numerous connections to the vertebral and branch veins, lack of valves in the internal and external venous plexus, marked venous enlargement in older individuals, and lower pressure in the vertebral venous system than in the pelvic veins [ 34 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the IVC and lumbar vein and characteristics of the lumbar vein need to be discerned, because intraoperative cement leakage into the IVC significantly contributes to PCE [ 68 ]. The lumbar veins enter the IVC at the L1-L5 vertebral positions, and cement flow into the IVC may result from the numerous connections to the vertebral and branch veins, lack of valves in the internal and external venous plexus, marked venous enlargement in older individuals, and lower pressure in the vertebral venous system than in the pelvic veins [ 34 , 68 , 69 ]. Iwanaga et al demonstrated that latex or air injections into the lumbar vertebral bodies drain specifically into the IVC and not internally into the vertebral venous plexus within the vertebral canal [ 70 ].…”
Section: Discussionmentioning
confidence: 99%